2012
DOI: 10.1039/c1jm14391c
|View full text |Cite
|
Sign up to set email alerts
|

Improved localized surface plasmon resonance biosensing sensitivity based on chemically-synthesized gold nanoprisms as plasmonic transducers

Abstract: Supporting substrate attached gold nanostructures display localized surface plasmon resonance (LSPR) properties at the visible and near-infrared (NIR) wavelengths. The LSPR wavelength is very responsive to the refractive index of the surrounding medium, allowing simple label-free biosensing when biomolecules are irreversibly adsorbed onto nanostructures. Herein, we show that chemically synthesized gold nanoprisms with 22 nm average edge lengths are very efficient plasmonic transducers for label-free biosensing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 66 publications
0
81
1
Order By: Relevance
“…The band at 530 nm is attributed to the byproducts of the Au nanoparticles. 44 From the SEM image and AFM measurement, it is found that the asprepared Au NPrs are flat NPs with three congruent edge lengths of 94 nm and thicknesses of 10 nm (Fig. 1b, c and e).…”
Section: Resultsmentioning
confidence: 99%
“…The band at 530 nm is attributed to the byproducts of the Au nanoparticles. 44 From the SEM image and AFM measurement, it is found that the asprepared Au NPrs are flat NPs with three congruent edge lengths of 94 nm and thicknesses of 10 nm (Fig. 1b, c and e).…”
Section: Resultsmentioning
confidence: 99%
“…A comparison of our experimental results with experimental data from selected conventional, non-integrated plasmonic structures for refractive index sensing shows that the sensitivity in our setup is markedly higher than what can be observed for plasmonic Au nanoparticles 12 and, in particular, exceeds the sensitivities typically obtained in Al nanohole arrays 27 (see table 1). 28 700 647 Au nanocross 29 1400 500 Au nanopillar 30 1300 -1500 1000 Periodic array of Au mushrooms 31 1260 1010 Hybrid Au nanohole array 15 650 -700 670 Suspended NHA in Au film 32 795 717 Passivated Al NHA 27 700 -750 487 This work 1310 -1350 1180 When the device is incorporated into a microfluidic setup with a laser diode as the vertical illumination light source 33 , the operating wavelength λop is fixed. In this operating mode, a resonance peak shift induced by a change in nSup can be detected as a change in responsivity at λop.…”
Section: Resultsmentioning
confidence: 99%
“…Triangular silver nanoplate is a powerful candidate within anisotropic plasmonic nanoparticles for constructing the chemical or biological sensors due to their thinness as compared to nanosphere, leading to a significant extension of the electromagnetic field farther from their surface. Furthermore, the three tips of the nanoplates with larger refractive index sensitivity dramatically contributes to their near-field electromagnetic enhancement localized the tips [33][34][35]. As shown in Fig.…”
Section: Deposition Of Plasmonic Nanoplates On the Bacteriamentioning
confidence: 95%